Розвиток творчого потенціалу майбутніх соціальних працівників у процесі вивчення курсу "Основи комунікації в соціальній роботі" - Равлюк, Тетяна (My University, 2017)
The theoretical and practical aspects of the creative potential of future social workers in the study course «Fundamentals of communication in social work». The notion of «individual creativity» and its main components. The composition of educational-methodical complex course «Fundamentals of communication in social work». A task for independent and individual student work aimed at promoting creativity. Features of evaluation results of creative activity of future social workers are overviewed
Keywords: an educational activity, individual creativity, focus on creative work, creative skills, characterological features, individual characteristics of mental processes